A numerical solution for Duffing-Van der Pol oscillators using a backward difference formulation - Rasedee A.F.N.; Sathar M.H.A.; Ijam H.M.; Othman K.I.; Ishak N.; Hamzah S.R. (American Institute of Physics Inc., 2024)
Indexed by WOS/ Scopus